The emerging role of neutrophil extracellular traps in the progression of rheumatoid arthritis - Chen, Jingjing; Cao, Yang; Xiao, Jing; Hong, Yujie; Zhu, Yan (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease with complex etiology. Neutrophil extracellular traps (NETsare NETswork protein structures activated by neutrophils to induce the cleavage and release of DNA-protein complexes.Current studies have shown the critical involvement of NETs in the progression of autoimmune diseases, Neutrophils mostly gather in the inflammatory sites of patients and participate in the pathogenesis of autoimmune diseases in various ways. NETs, as the activated state of neutrophils, have attracted much attention in immune diseases. Many molecules released in NETs are targeted autoantigens in autoimmune, such as histones, citroline peptides, MPO, etc. All of these suggest that NETs have a direct causal relationship between the production of autoantigens and autoimmune diseases. Especially for RA, as a disorder of innate and adaptive immune response, the pathogenesis of RA is inseparable from the generation of RA. In this paper, we investigate the emerging role of NETs in the pathogenesis of RA and suggest that NETs may be an important target for the treatment of inflammatory autoimmune diseases.